2014
DOI: 10.1038/srep04927
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Warburg effect – dual metabolic nature of cancer cells

Abstract: Warburg effect is a dominant phenotype of most cancer cells. Here we show that this phenotype depends on its environment. When cancer cells are under regular culture condition, they show Warburg effect; whereas under lactic acidosis, they show a nonglycolytic phenotype, characterized by a high ratio of oxygen consumption rate over glycolytic rate, negligible lactate production and efficient incorporation of glucose carbon(s) into cellular mass. These two metabolic modes are intimately interrelated, for Warburg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(181 citation statements)
references
References 52 publications
12
168
1
Order By: Relevance
“…Lactate is a critical substrate for supplying energy in cancer (via the Warburg effect), and is believed to help determine low pH during carcinogenesis (21). Furthermore, the activation of aerobic glycolysis can trigger lactate production, and as a byproduct, it can also supply nicotinamide adenine dinucleotide (NAD) + as a co-substrate for glycolysis which induce rapid cancer cell growth (22).…”
Section: U87mg Cells Favor Aerobic Glycolysis At the Transcriptional mentioning
confidence: 99%
“…Lactate is a critical substrate for supplying energy in cancer (via the Warburg effect), and is believed to help determine low pH during carcinogenesis (21). Furthermore, the activation of aerobic glycolysis can trigger lactate production, and as a byproduct, it can also supply nicotinamide adenine dinucleotide (NAD) + as a co-substrate for glycolysis which induce rapid cancer cell growth (22).…”
Section: U87mg Cells Favor Aerobic Glycolysis At the Transcriptional mentioning
confidence: 99%
“…The fluxes were reflected by the amount of generated lactate. The amounts of generated lactate were determined by HPLC as described by us previously (25). For PKM2, assay, the condition was the same as above except that ADP concentration in the in vitro glycolytic system was 50 M.…”
Section: Metabolic Flux Control Assaymentioning
confidence: 99%
“…The action was terminated by adding 600 l 1 M HClO 4 , then neutralized with 100 l 3 M K 2 CO 3 , After keeping on ice for about 30 min and centrifugation, the supernatant obtained was analyzed for the lactate generated. When PKM2 was assayed, the reaction mixture was the same as above, except ADP was 50 M. The amounts of generated lactate were determined by HPLC as described by us previously (25).…”
Section: In Vitro Glycolytic Systemmentioning
confidence: 99%
“…The metabolic shift to a higher rate of glycolysis can even be observed in patients with malignant tumors using positron emission tomography (PET) [5] . Beyond the current concept that the Warburg effect plays a central role in tumor metabolism, studies have shown that there may be dual metabolic (the Warburg effect and the nonglycolytic phenotype) natures in a given cell type, providing them with survival and growth advantages when adapting to a stressful microenvironment [6] . Cancer cells exhibit a glycolytic phenotype under regular conditions but can switch to a non-glycolytic phenotype under lactic acidosis.…”
Section: The Warburg Effect-a Hallmark Of Cancermentioning
confidence: 99%
“…In recent years, the concept of reversing the Warburg effect offers new perspectives to develop therapeutic strategies that focus on both of the targets, glycolysis and mitochondrial OXPHOS. Cancer cells can activate NFB and HIF-1α in adjacent stromal fibroblasts via oxidative stress promoted by ROS production, resulting in autophagy and mitophagy as well as glycolysis, which in turn can supply recycled nutrients to tumor cells for growth [6,55] . Therefore, it may be of significance to regulate glycolysis by targeting autophagy in the stroma.…”
Section: Anti-cancer Therapy Based On the Warburg Effectmentioning
confidence: 99%